Every Breath You Take: Non-invasive Real-Time Oxygen Biosensing in Two- and Three-Dimensional Microfluidic Cell Models - Zirath, Helene; Rothbauer, Mario; Spitz, Sarah; Bachmann, Barbara; Jordan, Christian; Müller, Bernhard; Ehgartner, Josef; Priglinger, Eleni; Mühleder, Severin; Redl, Heinz; Holnthoner, Wolfgang; Harasek, Michael; et al. (Frontiers in Physiology, 2018)
Knowledge on the availability of dissolved oxygen inside microfluidic cell culture systems is vital for recreating physiological-relevant microenvironments and for providing reliable and reproducible measurement conditions. It is important to highlight that in vivo cells experience a diverse range of oxygen tensions depending on the resident tissue type, which can also be recreated in vitro using specialized cell culture instruments that regulate external oxygen concentrations. While cell-culture conditions can be readily adjusted using state-of-the-art incubators, the control of physiological-relevant microenvironments within the microfluidic chip however, requires the integration of oxygen sensors. Although several sensing approaches have been reported to monitor oxygen levels in the presence of cell monolayers, oxygen demands of microfluidic 3D-cell cultures and spatio-temporal variations of oxygen concentrations inside 2D and 3D cell culture systems are still largely unknown. To gain a better understanding on available oxygen levels inside organ-on-a-chip systems, we have therefore developed two different microfluidic devices containing embedded sensor arrays to monitor local oxygen levels to investigate (a) oxygen consumption rates of 2D and 3D hydrogel-based cell cultures, (b) the establishment of oxygen gradients within cell culture chambers and (c) influence of microfluidic material (e.g. gas tight vs gas permeable), surface coatings, cell densities and medium flow rate on the respiratory activities of four different cell types. We demonstrate how dynamic control of cyclic normoxic-hypoxic cell microenvironments can be readily accomplished using programmable flow profiles employing both gas-impermeable and gas-permeable microfluidic biochips.